Adaptasi Agronomis Tiga Varietas Sorgum Manis (Sorghum bicolor L.) Terhadap Dua Agroekologi Lahan Kering di Pulau Lombok, Indonesia - Fahrudin Fahrudin; Suwardji Suwardji; Lalu Sukardi; Sukartono Sukartono; I Gusti Lanang Parta Tanaya; Tri Rachmanto (Jurnal Penelitian Pendidikan IPA, 2026)
Lombok Island, Indonesia, possesses approximately 893,758 ha of dryland with significant potential for developing drought-tolerant crops such as sweet sorghum (Sorghum bicolor L.) to strengthen food security in semi-arid regions. This study evaluated the agronomic adaptation of three sweet sorghum varieties, namely Bioguma 3, Soper 9, and Numbu, under two contrasting dryland agroecosystems: clay-textured Vertisol in East Lombok (pH 6.8, organic C 2.2%, CEC 64.6 me/100 g) and sandy loam Entisol in North Lombok (pH 6.3, organic C 1.0%, CEC 15.9 me/100 g). The experiment employed a randomized complete block design with four replications, observing stem biomass, leaf biomass, and grain yield at 75, 90, and 105 DAS. Results demonstrated that soil physical and chemical properties strongly influenced varietal performance. The Vertisol soil, characterized by high cation exchange capacity and moisture retention, significantly enhanced vegetative growth, with Bioguma 3 producing the highest stem biomass (75.00 tons/ha) and leaf biomass (8.18 tons/ha). In contrast, the Entisol soil generated lower biomass yields (41.64 tons/ha stems and 5.55 tons/ha leaves) but supported more stable grain production across varieties. Soper 9 recorded the highest grain yield, reaching 6.09 tons/ha on Vertisol and 4.70 tons/ha on Entisol. These findings highlight the importance of integrating appropriate varietal selection with soil management strategies to improve dryland agricultural productivity and promote sustainable food security.